Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Explore a wealth of knowledge from professionals across different disciplines on our comprehensive platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
Given that [tex]\(\tan x = -\frac{8}{15}\)[/tex] and [tex]\(x\)[/tex] terminates in quadrant II, we will find [tex]\(\sin 2x\)[/tex], [tex]\(\cos 2x\)[/tex], and [tex]\(\tan 2x\)[/tex].
First, we need to determine the values of [tex]\(\sin x\)[/tex] and [tex]\(\cos x\)[/tex] based on the tangent value.
### Finding [tex]\(\cos x\)[/tex] and [tex]\(\sin x\)[/tex]:
Using the identity:
[tex]\[ 1 + \tan^2 x = \sec^2 x \][/tex]
Given [tex]\(\tan x = -\frac{8}{15}\)[/tex]:
[tex]\[ 1 + \left(-\frac{8}{15}\right)^2 = \sec^2 x \][/tex]
[tex]\[ 1 + \frac{64}{225} = \sec^2 x \][/tex]
[tex]\[ \sec^2 x = \frac{225}{225} + \frac{64}{225} = \frac{289}{225} \][/tex]
So, [tex]\(\sec x = \sqrt{\frac{289}{225}} = \frac{17}{15}\)[/tex].
Since [tex]\(\sec x = \frac{1}{\cos x}\)[/tex]:
[tex]\[ \cos x = \frac{15}{17} \][/tex]
However, since [tex]\(x\)[/tex] is in quadrant II, [tex]\(\cos x\)[/tex] is negative:
[tex]\[ \cos x = -\frac{15}{17} \][/tex]
Next, using the Pythagorean identity:
[tex]\[ \sin^2 x + \cos^2 x = 1 \][/tex]
Since we already have [tex]\(\cos x = -\frac{15}{17}\)[/tex]:
[tex]\[ \sin^2 x + \left(-\frac{15}{17}\right)^2 = 1 \][/tex]
[tex]\[ \sin^2 x + \frac{225}{289} = 1 \][/tex]
[tex]\[ \sin^2 x = 1 - \frac{225}{289} \][/tex]
[tex]\[ \sin^2 x = \frac{289}{289} - \frac{225}{289} \][/tex]
[tex]\[ \sin^2 x = \frac{64}{289} \][/tex]
Thus:
[tex]\[ \sin x = \sqrt{\frac{64}{289}} = \frac{8}{17} \][/tex]
Since [tex]\(x\)[/tex] terminates in quadrant II, [tex]\(\sin x\)[/tex] is positive:
[tex]\[ \sin x = \frac{8}{17} \][/tex]
### Finding [tex]\(\sin 2x\)[/tex] and [tex]\(\cos 2x\)[/tex]:
Using the double angle identities:
[tex]\[ \sin 2x = 2 \sin x \cos x \][/tex]
[tex]\[ \sin 2x = 2 \left(\frac{8}{17}\right) \left(-\frac{15}{17}\right) \][/tex]
[tex]\[ \sin 2x = 2 \left(-\frac{120}{289}\right) \][/tex]
[tex]\[ \sin 2x = -\frac{240}{289} \][/tex]
Next, for [tex]\(\cos 2x\)[/tex]:
[tex]\[ \cos 2x = \cos^2 x - \sin^2 x \][/tex]
[tex]\[ \cos 2x = \left(-\frac{15}{17}\right)^2 - \left(\frac{8}{17}\right)^2 \][/tex]
[tex]\[ \cos 2x = \frac{225}{289} - \frac{64}{289} \][/tex]
[tex]\[ \cos 2x = \frac{225 - 64}{289} \][/tex]
[tex]\[ \cos 2x = \frac{161}{289} \][/tex]
### Finding [tex]\(\tan 2x\)[/tex]:
Finally, using the identity:
[tex]\[ \tan 2x = \frac{\sin 2x}{\cos 2x} \][/tex]
[tex]\[ \tan 2x = \frac{-\frac{240}{289}}{\frac{161}{289}} \][/tex]
[tex]\[ \tan 2x = \frac{-240}{161} \][/tex]
Rewriting it as a simplified fraction:
[tex]\[ \tan 2x = -\frac{240}{161} \][/tex]
Thus, the values are:
[tex]\[ \sin 2x = -\frac{240}{289} \][/tex]
[tex]\[ \cos 2x = \frac{161}{289} \][/tex]
[tex]\[ \tan 2x = -\frac{240}{161} \][/tex]
First, we need to determine the values of [tex]\(\sin x\)[/tex] and [tex]\(\cos x\)[/tex] based on the tangent value.
### Finding [tex]\(\cos x\)[/tex] and [tex]\(\sin x\)[/tex]:
Using the identity:
[tex]\[ 1 + \tan^2 x = \sec^2 x \][/tex]
Given [tex]\(\tan x = -\frac{8}{15}\)[/tex]:
[tex]\[ 1 + \left(-\frac{8}{15}\right)^2 = \sec^2 x \][/tex]
[tex]\[ 1 + \frac{64}{225} = \sec^2 x \][/tex]
[tex]\[ \sec^2 x = \frac{225}{225} + \frac{64}{225} = \frac{289}{225} \][/tex]
So, [tex]\(\sec x = \sqrt{\frac{289}{225}} = \frac{17}{15}\)[/tex].
Since [tex]\(\sec x = \frac{1}{\cos x}\)[/tex]:
[tex]\[ \cos x = \frac{15}{17} \][/tex]
However, since [tex]\(x\)[/tex] is in quadrant II, [tex]\(\cos x\)[/tex] is negative:
[tex]\[ \cos x = -\frac{15}{17} \][/tex]
Next, using the Pythagorean identity:
[tex]\[ \sin^2 x + \cos^2 x = 1 \][/tex]
Since we already have [tex]\(\cos x = -\frac{15}{17}\)[/tex]:
[tex]\[ \sin^2 x + \left(-\frac{15}{17}\right)^2 = 1 \][/tex]
[tex]\[ \sin^2 x + \frac{225}{289} = 1 \][/tex]
[tex]\[ \sin^2 x = 1 - \frac{225}{289} \][/tex]
[tex]\[ \sin^2 x = \frac{289}{289} - \frac{225}{289} \][/tex]
[tex]\[ \sin^2 x = \frac{64}{289} \][/tex]
Thus:
[tex]\[ \sin x = \sqrt{\frac{64}{289}} = \frac{8}{17} \][/tex]
Since [tex]\(x\)[/tex] terminates in quadrant II, [tex]\(\sin x\)[/tex] is positive:
[tex]\[ \sin x = \frac{8}{17} \][/tex]
### Finding [tex]\(\sin 2x\)[/tex] and [tex]\(\cos 2x\)[/tex]:
Using the double angle identities:
[tex]\[ \sin 2x = 2 \sin x \cos x \][/tex]
[tex]\[ \sin 2x = 2 \left(\frac{8}{17}\right) \left(-\frac{15}{17}\right) \][/tex]
[tex]\[ \sin 2x = 2 \left(-\frac{120}{289}\right) \][/tex]
[tex]\[ \sin 2x = -\frac{240}{289} \][/tex]
Next, for [tex]\(\cos 2x\)[/tex]:
[tex]\[ \cos 2x = \cos^2 x - \sin^2 x \][/tex]
[tex]\[ \cos 2x = \left(-\frac{15}{17}\right)^2 - \left(\frac{8}{17}\right)^2 \][/tex]
[tex]\[ \cos 2x = \frac{225}{289} - \frac{64}{289} \][/tex]
[tex]\[ \cos 2x = \frac{225 - 64}{289} \][/tex]
[tex]\[ \cos 2x = \frac{161}{289} \][/tex]
### Finding [tex]\(\tan 2x\)[/tex]:
Finally, using the identity:
[tex]\[ \tan 2x = \frac{\sin 2x}{\cos 2x} \][/tex]
[tex]\[ \tan 2x = \frac{-\frac{240}{289}}{\frac{161}{289}} \][/tex]
[tex]\[ \tan 2x = \frac{-240}{161} \][/tex]
Rewriting it as a simplified fraction:
[tex]\[ \tan 2x = -\frac{240}{161} \][/tex]
Thus, the values are:
[tex]\[ \sin 2x = -\frac{240}{289} \][/tex]
[tex]\[ \cos 2x = \frac{161}{289} \][/tex]
[tex]\[ \tan 2x = -\frac{240}{161} \][/tex]
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.